2020
DOI: 10.3390/ijms21239095
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Pro-Inflammatory and Calcium Handling Remodeling Underlies Spontaneous Onset of Paroxysmal Atrial Fibrillation in JDP2-Overexpressing Mice

Abstract: Background: Cardiac-specific JDP2 overexpression provokes ventricular dysfunction and atrial dilatation in mice. We performed in vivo studies on JDP2-overexpressing mice to investigate the impact of JDP2 on the predisposition to spontaneous atrial fibrillation (AF). Methods: JDP2-overexpression was started by withdrawal of a doxycycline diet in 4-week-old mice. The spontaneous onset of AF was documented by ECG within 4 to 5 weeks of JDP2 overexpression. Gene expression was analyzed by real-time RT-PCR and West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…In a previous study, tumor angiogenesis was proven to have a positive correlation with many solid tumors, such as lung cancer, colorectal cancer, gastric cancer, and breast cancer [ 13 , 14 ]. Important predictive diagnostic and prognostic biomarkers of angiogenesis-related genes have been identified in some malignancies, including liver cancer, colorectal cancer, gastric cancer and urothelial cancer [ 15 17 ]. Thus, the correlation of the angiogenesis gene signature and clinical outcomes or clinical relevance needs to be elucidated in LUAD patients.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, tumor angiogenesis was proven to have a positive correlation with many solid tumors, such as lung cancer, colorectal cancer, gastric cancer, and breast cancer [ 13 , 14 ]. Important predictive diagnostic and prognostic biomarkers of angiogenesis-related genes have been identified in some malignancies, including liver cancer, colorectal cancer, gastric cancer and urothelial cancer [ 15 17 ]. Thus, the correlation of the angiogenesis gene signature and clinical outcomes or clinical relevance needs to be elucidated in LUAD patients.…”
Section: Introductionmentioning
confidence: 99%
“…7 C). To further elaborate the sponge effect, we investigated a well-studied lncRNA MALAT1 which has been shown to interact with numerous RBPs 84 88 . As illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7 D, we observed that POP-seq captured peaks were sparsely distributed along the length of MALAT1 in contrast to the fairly uniform distribution of total RNA-seq reads showing higher expression of MALAT1 in K562 cells. We also included a track of ENCODE eCLIP peaks for RNA binding proteins HNRNPA1 and PTBP1 with known binding to MALAT1 84 shown in Fig. 7 D. The results suggest that HNRNPA1 and PTBP1 are most likely being sponged by highly expressed lncRNA MALAT1 in K562 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Кроме визуализирующих методик предсердий, таких как спекл-трекинг при выполнении эхокар-диографии (ЭхоКГ), компьютерной и магнитно-резонансной томографии, в качестве потенциальных диагностических инструментов ПКМП изучались маркеры воспаления (C-реактивный протеин, цитокины), миокардиального стресса, молекулы адгезии и факторы коагуляции, а также показатели системы коллагенолиза, но преимущественно отдельно у лиц с ФП или СД [8]. НУП изучались преимущественно в диагностике ХСН, хотя теоретически их роль в выявлении ПКМП может быть приоритетной [9].…”
Section: Discussionunclassified